2017
DOI: 10.2147/ijn.s138641
|View full text |Cite
|
Sign up to set email alerts
|

Biotransport kinetics and intratumoral biodistribution of malonodiserinolamide-derivatized [60]fullerene in a murine model of breast adenocarcinoma

Abstract: [60]Fullerene is a highly versatile nanoparticle (NP) platform for drug delivery to sites of pathology owing to its small size and both ease and versatility of chemical functionalization, facilitating multisite drug conjugation, drug targeting, and modulation of its physicochemical properties. The prominent and well-characterized role of the enhanced permeation and retention (EPR) effect in facilitating NP delivery to tumors motivated us to explore vascular transport kinetics of a water-soluble [60]fullerene d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
5
20
1
1
Order By: Relevance
“…The DLS measurements showed that C 60 -NOTA conjugate forms uniform aggregates in water with an average diameter of 182 nm and an average polydispersity index of 0.27. These results agreed with the aggregate size that C 60 -serinol itself has shown to form in aqueous solution (median aggregate size 100-200 nm) [47]. These DLS results were also in good agreement with the aggregate size found in the solid state as determined by atomic force microscopy (AFM) images ( Figure S11) which showed the average aggregate size to be 195 nm.…”
Section: Synthesis and Characterization Of C 60 -Nota Conjugatesupporting
confidence: 86%
See 2 more Smart Citations
“…The DLS measurements showed that C 60 -NOTA conjugate forms uniform aggregates in water with an average diameter of 182 nm and an average polydispersity index of 0.27. These results agreed with the aggregate size that C 60 -serinol itself has shown to form in aqueous solution (median aggregate size 100-200 nm) [47]. These DLS results were also in good agreement with the aggregate size found in the solid state as determined by atomic force microscopy (AFM) images ( Figure S11) which showed the average aggregate size to be 195 nm.…”
Section: Synthesis and Characterization Of C 60 -Nota Conjugatesupporting
confidence: 86%
“…The ζ-potential of C 60 -NOTA and C 60 -Cu(NOTA) were also investigated to determine the surface charge on the conjugate, which can affect the biodistribution of the material [49]. The ζ-potential of C 60 -NOTA and C 60 -Cu(NOTA) were −22.5 mV and −11.4 mV, respectively, which agrees well with ζ-potential measurements of C 60 -serinol and other water soluble C 60 materials [39,47,50]. The C60-NOTA conjugate was then chelated with nonradioactive Cu 2+ to demonstrate the chelating ability of NOTA while appended to the C60 cage.…”
Section: Synthesis and Characterization Of C 60 -Nota Conjugatesupporting
confidence: 69%
See 1 more Smart Citation
“…1 Chemical structure of nanoC 60 -GEM file 1: Fig. S4), and which may be disintegrated into smaller individual fullerenes inside the cell (Lapin et al 2017b). The zeta potential measurements of our gemcitabine nanoconjugate (Additional file 1: Fig.…”
Section: Synthetic Protocol and Characterization Of Nanoc 60 Gemmentioning
confidence: 99%
“…В частности, прижизненная микроскопия применя-лась для изучения внутриутробной кинетики био-трансляции производного C 60 -ser, вводимого вну-тривенно, в подкожных опухолях рака груди 4T1-luc в сравнении с нормальной тканью у живых мышей. Конъюгация C 60 -ser с флуоресцентным красителем PromoFluoro-633 (C 60 -serPF) позволила отслеживать флуоресценцию и относительную количественную оценку C 60 -ser in vivo [99]. Авторы считают, что, по-скольку этот флуорофор (~ 650 Да) сопоставим по размеру и структуре с низкомолекулярными препа-ратами для лечения рака, такими как паклитаксел (854 Да), его можно рассматривать как стерически модельный препарат для исследования C 60 -serPF в качестве носителя лекарственного средства.…”
Section: токсичность биостабильность и биораспределение фуллеренов иunclassified